THE FIRST-ORDER COHOMOLOGY GROUP OF SOME COMMUTATIVE SEMIGROUP ALGEBRAS (Journal of Academic Research, 2019)
In this paper we calculate the first-order cohomology group , where  is a commutative, 0-cancellative, -semigroup.